Workload, job satisfaction, and salary satisfaction with turnover intention of health workers - Wa Ode Novi Angraeni; Suprapto Suprapto; Suliman Alshammari (Edukasi Ilmiah Indonesia, 2025)
promotive and preventive efforts. The implementation of the Regional Public Service Agency Financial Management Pattern (PPK-BLUD) provides flexibility in resource management, including the recruitment of contract workers. However, high workloads, low job satisfaction, and dissatisfaction with salaries can trigger turnover intentions of health workers, which has an impact on service quality and organizational stability. Research Methodology: This study uses a cross-sectional design with a quantitative approach. The research population includes all health workers with BLUD contract status from 37 health centers, and it includes as many as 418 people. The sample was taken using a simple random sampling technique, resulting in 204 respondents who met the inclusion criteria, namely, having worked for more than 6 months. Multiple linear regression tests were carried out for data analysis. Results: The results of the analysis using multiple linear regression showed that there was a significant relationship between workload and turnover intention (p = 0.001), as well as a significant relationship between job satisfaction and turnover intention (p = 0.043) in BLUD contract health workers. Meanwhile, satisfaction with salary showed no significant relationship with turnover intention (p = 0.169). These findings indicate that high workloads and low job satisfaction contribute to the increased willingness of healthcare workers to leave their jobs. In contrast, salary satisfaction levels are not the dominant factor in determining these intentions. Conclusion: This study shows that workload and job satisfaction have a significant relationship with the turnover intention of health workers under BLUD contracts, while salary satisfaction has no significant effect. Therefore, good human resource planning, workload management, and increased job satisfaction are important strategies for suppressing exit intentions and maintaining the sustainability and quality of services at the Health Center